1999
DOI: 10.1111/j.1349-7006.1999.tb00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotype Difference of Aldehyde Dehydrogenase 2 Gene in Alcohol Drinkers Influences the Incidence of Japanese Colorectal Cancer Patients

Abstract: A case-control study was conducted to explore the possible etiologic role of alcohol and aldehyde dehydrogenase 2 (ALDH2) gene among Japanese colorectal cancer patients. Information on their drinking, smoking and dietary habits was collected from 265 colon and 164 rectum cancer patients, and 794 non-cancer patients as a control group. Genotypes of the ALDH2 gene at codon 487, glutamic acid (ALDH2 * 1) as a wild-type or lysine (ALDH2 * 2) as a mutated type with reduced enzyme activity, were analyzed by polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 27 publications
2
47
1
1
Order By: Relevance
“…The ORs for the highest category of consumption vs the lowest are summarized in Figure 1. Out of 11 case -control studies, three found a significant risk increase (Benito et al, 1990;Iscovich et al, 1992;Steinmetz & Potter, 1993) and three other studies a significantly decreased risk (Shannon et al, 1996;Kampman et al, 2000;Murata et al, 1999). The diversity of dairy products may to some extent explain the inconsistencies of these results.…”
Section: Total Dairy Productsmentioning
confidence: 98%
“…The ORs for the highest category of consumption vs the lowest are summarized in Figure 1. Out of 11 case -control studies, three found a significant risk increase (Benito et al, 1990;Iscovich et al, 1992;Steinmetz & Potter, 1993) and three other studies a significantly decreased risk (Shannon et al, 1996;Kampman et al, 2000;Murata et al, 1999). The diversity of dairy products may to some extent explain the inconsistencies of these results.…”
Section: Total Dairy Productsmentioning
confidence: 98%
“…However, the results have been inconsistent (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The present comprehensive meta-analysis of currently published studies aimed to identify the relationships between the ADH1B and ALDH2 polymorphisms and the risk of CRC.…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, low ALDH levels in the colon lead to the highest acetaldehyde exposure of any tissue during ethanol metabolism, which is believed to be a factor in alcohol-related colon cancer (Salaspuro 1996). ALDH2-mediated metabolism of acetaldehyde is a major detoxification route, and carriers of the ALDH2*2 polymorphism, which confers loss of ALDH2 enzymatic activity, have increased risk for alcohol-related colon cancer (Murata et al 1999) and smoke-and alcohol-related lung cancer (Minegishi et al 2007;Eom et al 2009). Although acetaldehyde itself is poorly metabolized by ALDH3B1, downstream LPO-derived aldehydes, including the highly cytotoxic 4-HNE, appear to be good substrates (Marchitti et al 2007b).…”
Section: Aldh3b1: Ihc Expression In Normal and Cancerous Tissuementioning
confidence: 99%